Q: How do you find b squared?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

a(squared)+b(squared)=c(squared) The largest number is the c, and you can choose the a and b, since you need to find the a or the b. For example: You have the numbers 3, and 5 and you needed to find b. a(squared+b(squared)=c(squared) 3(squared)+b(squared)=5(squared) 9+b(squared)=25 -9 -9 b(squared)=16 Then take the square root b=4

a=b=3.60555

The great pythagorean theorm: a(squared) + b(squared) = c(squared)

a triangle has 3 sides. the longest side is always C. the other 2 are A and B (which one is which doesn't matter). u can find side C using A squared plus B squared equals C squared. It's basically AxA + BxB =CxC. to find side A, use C squared minus B squared. CxC - BxB = AxA . To find B, use the same equation to find A except switch B with A. CxC - AxA = BxB.-Mathnerd157

A squared+ B squared=C squared. find the square root of the answer and you get the longest side.

Related questions

a(squared)+b(squared)=c(squared) The largest number is the c, and you can choose the a and b, since you need to find the a or the b. For example: You have the numbers 3, and 5 and you needed to find b. a(squared+b(squared)=c(squared) 3(squared)+b(squared)=5(squared) 9+b(squared)=25 -9 -9 b(squared)=16 Then take the square root b=4

a=b=3.60555

B squared equals c squared minus a squared then to find B take the square root of you answer for b squared

To find the answer of a triangle You do A squared+ B squared= C squared

if you mean a right triangle then the formula is a squared + b squared = c squared. a and b are the legs and c is the hypotunese. the legs are the smallest number then the hypotenese. An example is a=3 , b= ? and c =5 use the formula : a squared + b squared = c squared 3 squared + b squared = 5 squared 9 + b squared = 25 -9 - 9 _________________________________________ b squared = 16 Then you have to take the squared root of 16 which is 4 and 4 is b squared.

The great pythagorean theorm: a(squared) + b(squared) = c(squared)

a triangle has 3 sides. the longest side is always C. the other 2 are A and B (which one is which doesn't matter). u can find side C using A squared plus B squared equals C squared. It's basically AxA + BxB =CxC. to find side A, use C squared minus B squared. CxC - BxB = AxA . To find B, use the same equation to find A except switch B with A. CxC - AxA = BxB.-Mathnerd157

the formula is a squared + b squared = c squared to find the hypotenuse (the longest side) find the square root of you previous answer.

A squared+ B squared=C squared. find the square root of the answer and you get the longest side.

The formula for finding the angles is called " Pythagorean Thyrum " It states that a squred plus b squared equals c squared so therefore c squared minus a squared will equal b squared. i hope that helps

he made the theorem C squared = A squared + B squared and A squared = C squared - B squared or B squared = C squared - A squared

It is: 2b squared